Hubungan Masa Kerja dan Dosis Pajanan Kebisingan Harian dengan Gangguan Pendengaran Pekerja Tambang Batu Bara PT.X - Rahmatunnisa, Dilenia; Duma, Krispinus; Tresnasari, Putri (Jurnal Medika : Karya Ilmiah Kesehatan, 2023)
Noise is one of physical hazard in coal mining and a cause of hearing loss. Hearing loss is a partial or complete loss of hearing in one or both ears. Several risk factors for hearing loss are work period and daily dose of noise exposure. This research aims to investigate the relationship between work period and daily dose of noise exposure with hearing loss in coal miners at PT.X. The research used analytical observational study design with cross-sectional study approach. The data on hearing loss among miners were collected from the result of audiometry at routine medical check-up held by the company, while the data work period were collected from HR and daily dose of noise exposure data were collected by measuring the dose of noise exposure using a purposive sampling method. The data were collected and selected using purposive sampling metdhod. 83 miners fulfilled the inclusion and exclusion criteria. The bivariate analysis was perfomed using Chi-Square test. The results of this research showed that there was a relationship between working period and hearing loss with p-value = 0.000 (p<0.05) and there was a relationship between daily dose of noise exposure and hearing loss with p-value = 0.001 (p <0.05). Keyword : Hearing Loss, Work Period, Daily Dose of Noise Exposure Mine